2021
DOI: 10.3389/fmed.2021.792689
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach for the Prediction of Traumatic Brain Injury Induced Coagulopathy

Abstract: Background: Traumatic brain injury-induced coagulopathy (TBI-IC), is a disease with poor prognosis and increased mortality rate.Objectives: Our study aimed to identify predictors as well as develop machine learning (ML) models to predict the risk of coagulopathy in this population.Methods: ML models were developed and validated based on two public databases named Medical Information Mart for Intensive Care (MIMIC)-IV and the eICU Collaborative Research Database (eICU-CRD). Candidate predictors, including demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Beyond fibrinolysis, ornithine has been described as a marker of endotheliopathy, competing with arginine as a substrate with nitric oxide synthase; the end result in the setting of TBI is that ornithine induces oxidative stress and decreases blood-brain barrier integrity 48 . Creatinine, another important metabolite in the arginine and proline pathway, significantly increased after dura violation in our population; in a previous study aimed to identify predictors of coagulopathy in TBI and develop machine learning (ML) models to predict the risk of coagulopathy, Yang et al found that creatinine was a core component in contributing to prediction of coagulopathy in TBI patients 1 …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Beyond fibrinolysis, ornithine has been described as a marker of endotheliopathy, competing with arginine as a substrate with nitric oxide synthase; the end result in the setting of TBI is that ornithine induces oxidative stress and decreases blood-brain barrier integrity 48 . Creatinine, another important metabolite in the arginine and proline pathway, significantly increased after dura violation in our population; in a previous study aimed to identify predictors of coagulopathy in TBI and develop machine learning (ML) models to predict the risk of coagulopathy, Yang et al found that creatinine was a core component in contributing to prediction of coagulopathy in TBI patients 1 …”
Section: Discussionmentioning
confidence: 86%
“…48 Creatinine, another important metabolite in the arginine and proline pathway, significantly increased after dura violation in our population; in a previous study aimed to identify predictors of coagulopathy in TBI and develop machine learning (ML) models to predict the risk of coagulopathy, Yang et al found that creatinine was a core component in contributing to prediction of coagulopathy in TBI patients. 1 To complement the metabolomic data which characterizes a shift toward platelet hyperactivity and fibrinolysis shutdown, our proteomic data demonstrated key increases in proteins related to platelet activation, degranulation, and aggregation which correlated to thrombelastographic measurements of platelet activity. Examining the mechanisms and natural history of TBI has been recently empowered by proteomic data, which has further characterized the neuroinflammatory response to TBI.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[18][19][20][21] Trauma-induced platelet dysfunction is well described. 7,22,23 In addition, although more recent work has tended to focus on the documentation and assessment of trauma-associated platelet dysfunction, plateletassociated disturbances-in function and numbersappear to be common and specific to TBI [24][25][26][27][28][29][30][31][32][33][34] but overall are frustratingly poorly correlated with clinical observations of bleeding. 35 However, despite the marked excess risk for TBI and TBI mortality with aging, 3,4 few studies have attempted to isolate the potential independent associations of age with platelet dysfunction in TBI, tending instead to bin such effects with medication and/or comorbidities and/or to bin TBI with other severe trauma.…”
Section: Discussionmentioning
confidence: 99%